DIURNAL VARIATIONS OF METEOROLOGICAL ELEMENTS TO FLUCTUATION OF AIR QUALITY PARAMETERS - Wandayantolis, Wandayantolis; Maslakah, Firda Amalia; Nugroho, Sugeng (UI Scholars Hub, 2023)
Many studies have shown the relationship between meteorological elements and air quality. However, some aspects of the relationship are unknown, particularly in Indonesia, which has a variety of topographical landscapes and climatic conditions. This study seeks to define the relationship between meteorological variables and the diurnal pattern of three pollutants that contributes to the so-called Indeks Standard Pencemar Udara (ISPU), similar to the Air Quality Index (AQI), in a remote area in Bukit Kototabang, West Sumatra, Indonesia. The three parameters, namely Particulate Matter 10 micrometers (PM10), carbon monoxide (CO), and tropospheric ozone (O3), were correlated with diurnal variations in temperature and relative humidity in the months of maximum rainfall and minimum rainfall in 2020. The T-test was used to obtain each parameter's mean and variance sizes and the significant differences among the parameters. The results showed that PM10 has a significant distribution when high and low rainfall, but no significant relationship exists between temperature and relative humidity. Carbon monoxide has significant fluctuations to differences in rainfall and diurnal variations in air temperature. Meanwhile, O3 shows a weak correlation to the rainfall variation but has a high correlation to diurnal variations in the temperature and relative humidity. The results suggest that air temperature can significantly affect the diurnal concentration of pollutants, which involves photochemical reactions in their formation, such as ozone and carbon monoxide. It also shows the potential for worse air quality during the low rainfall. As the pollutant level can be higher during the dry season compared to the rainy season, efforts to reduce the pollutant emission during the dry season, like forest and land fires, need to gain more attention.